2014
DOI: 10.1007/s10508-014-0268-4
|View full text |Cite
|
Sign up to set email alerts
|

Explaining the Suicide Risk of Sexual Minority Individuals by Contrasting the Minority Stress Model with Suicide Models

Abstract: Many studies have found elevated levels of suicide ideation and attempts among sexual minority (homosexual and bisexual) individuals as compared to heterosexual individuals. The suicide risk difference has mainly been explained by minority stress models (MSTM), but the application of established suicidological models and testing their interrelations with the MSTM has been lacking so far. Therefore, we have contrasted two established models explaining suicide risk, the Interpersonal Psychological Theory (IPT) (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
110
1
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(135 citation statements)
references
References 39 publications
19
110
1
5
Order By: Relevance
“…These areas represent opportunities for future research. In general, suicide research regarding gender and sexual minorities has tended to overlook existing theoretical frameworks within suicidology [57], though they are not incompatible with other frameworks or methods. Future research with trans populations could draw on interdisciplinary theories as well as evidence from trans-specific and broader population research on suicide ideation and attempts to study mediated pathways.…”
Section: Discussionmentioning
confidence: 99%
“…These areas represent opportunities for future research. In general, suicide research regarding gender and sexual minorities has tended to overlook existing theoretical frameworks within suicidology [57], though they are not incompatible with other frameworks or methods. Future research with trans populations could draw on interdisciplinary theories as well as evidence from trans-specific and broader population research on suicide ideation and attempts to study mediated pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent results were found in a more recent study of 876 lesbian, gay, and bisexual adolescents from three U.S. cities: Perceived burdensomeness was the critical mechanism for explaining depression and suicidal ideation (Baams, Grossman, & Russell, 2015). Finally, Plöderl and colleagues (2014) found that perceived burdensomeness, thwarted belongingness, and acquired capability were each significantly correlated with suicidal ideation among both sexual minority and heterosexual groups.…”
Section: Interpersonal Psychological Theory Of Suicidementioning
confidence: 92%
“…Social ostracism has been suggested to be an important risk factor that contributes to increased psychological distress in gender diverse adolescents [1720]. Likewise, in sexual minorities, factors of social ostracism (such as peer exclusion or peer rejection) were linked to an elevated risk of self-harming thoughts and behaviours [2123]. It is still unclear to what extent social ostracism influences the presence of psychopathology in gender diverse adolescents and what role contextual factors may play in their mental health.…”
Section: Introductionmentioning
confidence: 99%